Celecoxib for the Prevention of Colorectal Adenomatous Polyps - Arber, Nadir; Eagle, Craig J; Spicak, Julius; Rácz, István; Dite, Petr; Hajer, Jan; Zavoral, Miroslav; Lechuga, Maria J; Gerletti, Paola; Tang, Jie; Rosenstein, Rebecca B; Macdonald, Katie; et al. (The New England journal of medicine, 2006)
Subjects who had a history of colonic adenomas were randomly assigned to three years of treatment with 400 mg of celecoxib or placebo once daily. Celecoxib significantly reduced the risk of adenomas (cumulative rate, 34 percent in the celecoxib group and 49 percent in the placebo group) and advanced adenomas (cumulative rate, 5 percent and 10 percent, respectively). Daily treatment with 400 mg of celecoxib over three years significantly reduced the risk of adenomas and advanced adenomas. Colorectal cancer, the second most prevalent cancer in the developed world and the third most prevalent in developing nations, 1 is responsible worldwide for more than a million new cases of cancer and half a million deaths annually. 2 Recent annual reductions of 1.8 percent in the incidence in the United States are credited, in part, to increased screening and the removal of adenomatous polyps (adenomas). 3 Most cases of colorectal cancer are preceded by adenomas, which are characterized by an early accumulation of gene mutations. 4 The regression and prevention of adenomas have become primary aims of investigators, who have used nonsteroidal antiinflammatory . . .